Casement Windows With and Without Screens: CFD Study on Lighting, Thermal, and Malaria - Cornelia Hildegardis (Nucleus Journal, 2026)
Despite growing evidence linking housing design to malaria transmission in sub-Saharan Africa, quantitative CFD-based evidence on window screen effects within the Indonesian context remains scarce, particularly in endemic districts such as Sikka Regency. This study evaluates the effect of casement windows with and without mosquito screens on natural lighting performance and thermal conditions in dwellings, and assesses the potential implications for indoor microclimate conditions relevant to malaria vector activity. A case study of a PUPR model house in Sikka Regency was conducted using direct field measurements and Computational Fluid Dynamics (CFD) simulations to analyze airflow, temperature, and humidity distributions under two window scenarios. Results showed that screened windows reduced average natural lighting from 96 lux to 87 lux and increased indoor relative humidity by 13.51% (up to 68.03%) compared to unscreened windows. Unscreened windows produced more effective cross ventilation, more stable indoor temperatures, and lower humidity—conditions less conducive to mosquito persistence. Conversely, screened windows restricted airflow, triggered stagnant air zones, raised local temperatures, and increased humidity, conditions that may increase the likelihood of mosquito persistence or presence indoors. These findings suggest that passive window design decisions carry significant implications for indoor microclimate quality in malaria-endemic tropical dwellings, and should be integrated into healthy housing design guidelines for endemic regions.